Metabolismo energético, resistência a insulina e produção de leite durante o periparto de vacas leiteiras com diferentes concentrações de bPL - Weschenfelder, Marina Menoncin (2013)
The bovine placental lactogen (bPL) acts favoring the entry and utilization of nutrients to the fetus through transient insulin resistance and also can have an indirect controll of lipolysis during prepartum via IGFs. The hypothesis of this study was that cows with great bPL and IGF-I concentration during the prepartum, has high NEB during postpartum period and higher insulin resistance to the same period. The aim of this experiment was determine the effects of different bPL concentrations on serum IGF-I and lipid mobilization, insulin resistance and milk yield in dairy cows. Twenty Holstein dairy cows on the third lactation, producing 30.65±8.2 L at 46 DIM and 658.10±89,2 Kg of live weight were used in this study at -21d until 28d related to calving. The IGF- I and NEFA serum concentration were evaluated. The cows were divided in three groups from their bPL concentration (LOW< 2.29ng/mL (n= 6), MED > 2.3 ng/mL e < 2.5 ng/mL (n= 7) e UP> 2.51 ng/mL (n= 7)). The data of BCS, milk yield and body weight were weekly evaluated. All animals were subjected to TTG on -9d and +9d relatives to calving day. Difference was observed on bPL (P = 0.0001) and IGF-I (P = 0.0002) levels between groups on prepartum period. During TTG was observed insulin AUC (t60-150) higher (P = 0.04) in LOW group compared with MED and UP. UP group have higher (P = 0.02) milk yield than MED group. It was concluded that bPL does not have any direct effect on lipolysis during the postpartum period, also it does not have any direct effect on synthesis of IGF-I levels, as well as it has positive effects on milk production and higher insulin sensibility.